The Nelayan Enterprise / Siti Aisyah Abdul Rahman - Siti Aisyah, Abdul Rahman (2020)
The Nelayan Enterprise is a company that providing fresh and high-quality seafood to our customers but at the affordable prices. We offered products that are very commonly used by our customers such as prawn, squid, and a variety of fish. We targeting customers among housewives and women as our main target market. We also provide online purchase besides customers can walk-in into our shop. Besides that, we can deliver customer's orders to their house. Our business need to be grown over the year. Our competitive advantages are we have the ability to manufacture products at the lowest cost. Besides that, our shop has a great geographical location because it can be reached easily. The management of The Nelayan Enterprise consist of 5 lead managers which are Aisyah, Dayana, Ramizah, Adriana, Muhammad Faiz, and Arif Amran. Our workers have extensive experience in accounting, finance, operating and sales marketing.6 of us will take the role responsible together even we have a different scope of work. After we produce the products and it gets a lot of attention from local, we will extend our business all over the Malaysia market. The Nelayan will always provide satisfaction to our beloved customers